Operation of a multipurpose reservoir system - case study of Feitsui Reservoir Project - Liu, Wen-shan; Bogardi, Janos J.; Wang, Tsan-Wen; Gupta, Ashim Das; R.O.C Government (Bangkok : Asian Institute of Technology, 1985)
The deterministic linear programming (DLP) and stochastic linear programming Linear Decision Rule (LDR) approaches are applied to finding the optimum operating policy of Feitsui Reservoir, Taiwan, R.O.C. An attempt is made to fully supply the water demand for the future 50 years and with this primary purpose to generate as much power a possible. After DLP and LDR are used as a tool for a screening study to find the optimum configuration of the system elements. This optimized configuration is then used as the starting point for the evaluation of the system by using a simulation method. 100 years of streamflow data were generated for LDR and for simulation purposes. The evaluation is made in order to examine the effect of streamflow variation on the system over a hydrological period over 29 years and 100 years generated hydrological data. The results obtained from this study indicated that the reservoir capacity is sufficient for public water supply purposes. The mean monthly hydropower generated can be a reference for the planning purpose. The operation policy from the different approach are presented as a reference for future operation.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1985
Keywords: Feitsui Reservoir Project